Individual behavioral variation reflects personality divergence in the upcoming model organism Nothobranchius furzeri - Thoré, Eli S. J. (John Wiley and Sons Inc., 2018)

(untitled) (Ecol Evol)
In the animal kingdom, behavioral variation among individuals has often been reported. However, stable among‐individual differences along a behavioral continuum—reflective of personality variation—have only recently become a key target of research. While a vast body of descriptive literature exists on animal personality, hypothesis‐driven quantitative studies are largely deficient. One of the main constraints to advance the field is the lack of suitable model organisms. Here, we explore whether N. furzeri could be a valuable model to bridge descriptive and hypothesis‐driven research to further unravel the causes, function and evolution of animal personality. As a first step toward this end, we perform a common garden laboratory experiment to examine if behavioral variation in the turquoise killifish Nothobranchius furzeri reflects personality divergence. Furthermore, we explore if multiple behavioral traits are correlated. We deliver “proof of principle” of personality variation among N. furzeri individuals in multiple behavioral traits. Because of the vast body of available genomic and physiological information, the well‐characterized ecological background and an exceptionally short life cycle, N. furzeri is an excellent model organism to further elucidate the causes and implications of behavioral variation in an eco‐evolutionary context.